2023
DOI: 10.1002/jcop.23008
|View full text |Cite
|
Sign up to set email alerts
|

Ecological promotive and protective factors deterring gun carriage for young adults living in communities with high rates of community violence

Abstract: This study identified promotive and protective factors that lessened the likelihood of handgun carriage in a sample of 141 predominantly Black (97%) young adults (ages 18–22) living in high burden communities experiencing elevated rates of violence. Participants completed surveys assessing overall risk and protective factors for violence across ecological contexts (e.g., individual/peer, family, school, and community). A series of regression and moderation analyses were conducted to ascertain direct (promotive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…Additionally, correlations between the study variables (with Bonferroni correction (p < .000125)) are presented in Table 1. A previous study with this dataset also found direct relations between ethnic identity and gun carriage such that young adults with higher ethnic identity were less likely to report carrying a gun (Ross et al, 2023).…”
Section: Direct Relationssupporting
confidence: 62%
See 4 more Smart Citations
“…Additionally, correlations between the study variables (with Bonferroni correction (p < .000125)) are presented in Table 1. A previous study with this dataset also found direct relations between ethnic identity and gun carriage such that young adults with higher ethnic identity were less likely to report carrying a gun (Ross et al, 2023).…”
Section: Direct Relationssupporting
confidence: 62%
“…At the individual-level, Carter et al (2020) found that positive coping skills and high self-efficacy were negatively related to gun carriage. A previous investigation (using the dataset in the current study) identified ethnic identity as a promotive factor for gun carriage (Ross et al, 2023). That study also identified protective factors including lack of family conflict, student status, and community assets that moderated relations between community violence exposure and the likelihood of gun carriage (Ross et al, 2023).…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations